Keselamatan Tanpa Sekat (Studi Hermeneutis Mengenai Konsep Keselamatan Universal Menurut Markus 7:24-30) - Raulina; Panjaitan, Geri Gabriel (Fidei: Jurnal Teologi Sistematika dan Praktika, 2025)
This study examines the narrative of the Syro-Phoenician woman in Mark 7:24-30 to understand the concept of universal salvation revealed by Jesus Christ in the context of His mission. This topic is important considering the tension between Jesus’ mission initially aimed at the people of Israel and the evidence that salvation is also intended for Gentiles without ethnic or social discrimination. The purpose of the study is to analyze how the dialogue between Jesus and the Syro-Phoenician woman affirms the universality of the gift of salvation that transcends social and ethnic boundaries. The method used is a historical-critical approach and textual exegesis by examining the historical, cultural context, and theological message of the narrative in depth. The research results show that the faith of the Syro-Phoenician woman serves as an indicator of the acceptance of the universality of salvation, affirming that God’s salvation is not limited by ethnic or social identity but depends on a sincere response of faith. These findings contribute to the understanding of inclusivity in church ministry in spreading the grace of salvation to all humanity with full conviction and hope. AbstrakPenelitian ini mengkaji narasi perempuan Siro-Fenisia dalam Markus 7:24-30 untuk memahami konsep keselamatan universal yang diungkapkan oleh Yesus Kristus dalam konteks misi-Nya. Topik ini penting mengingat adanya ketegangan antara misi Yesus yang awalnya ditujukan kepada bangsa Israel dengan bukti bahwa keselamatan juga diperuntukkan bagi orang non-Yahudi tanpa diskriminasi etnis maupun sosial. Tujuan penelitian adalah menganalisis bagaimana dialog antara Yesus dan perempuan Siro-Fenisia menegaskan universalitas anugerah keselamatan yang melampaui batas-batas sosial dan etnis. Metode yang digunakan adalah pendekatan historis-kritis dan eksegesis teks dengan menelaah konteks historis, budaya, serta pesan teologis narasi tersebut secara mendalam. Hasil penelitian menunjukkan bahwa iman perempuan Siro-Fenisia menjadi indikator penerimaan universalitas keselamatan, yang menegaskan bahwa keselamatan Allah tidak terbatas oleh identitas etnis atau sosial, melainkan bergantung pada respons iman yang sungguh-sungguh. Temuan ini memberikan kontribusi pada pemahaman inklusivitas pelayanan gereja dalam menyebarkan kasih karunia keselamatan kepada seluruh umat manusia dengan penuh keyakinan dan harapan.